Kafka Streams with Spring Cloud Stream - Pandey, Prashant (Packt Publishing, 2021)
Master real-time stream processing microservices with Kafka Streams and Spring cloud streams. About This Video Explore Kafka Streams with JSON, AVRO, and other custom serialization Learn Kafka architecture and programming with Kafka Streams API Understand how to build applications using Spring Boot with streaming data In Detail Kafka Streams with Spring Cloud Streams will help you understand stream processing in general and apply it to Kafka Streams Programming using Spring Boot. This course uses the Kafka Streams library compatible with Spring Cloud 2020. All the source code and examples used in this course have been tested by the author on Confluent Platform 6.0.0, which is compatible with Apache Kafka 2.6 open-source distribution. This is a fully example-driven course, and you will be working with multiple examples during the entire session. We will be making extensive use of IntelliJ IDEA as the preferred development IDE and Apache Maven and Gradle as the preferred build tool. However, based on your prior experience, you should be able to work with any other IDE designed for Spring application development and any other build tool designed for Java applications. This course also makes use of Log4J2 to teach you industry-standard log implementation in your application. We will be using JUnit5, which is the latest version of JUnit, to implement unit test cases. Working examples and exercises are the most critical tool to sharpen your skills. This course consists of some programming assignments as and when appropriate. These exercises will help you validate and check your concepts and apply your learning to solve programming problems.
Online resource; Title from title screen (viewed July 26, 2021)
Keywords: Streaming video; Internet videos; Vidéo en continu; Vidéos sur Internet; streaming video; Electronic videos